Practical Enzymology - Bisswanger, Hans (WILEY-VCH, 2004)
Providing a broad experimental approach, this book contains a theoretical introduction together with practical protocols, considering all aspects of enzymology. The fundamental experiments in enzymology are presented in very clear and easily realizable protocols, with each experiment accompanied by a section giving the theoretical background.